An observational study for evaluation of antibiotic utilization and growing resistance against antibiotics in pediatric patients suffering from meningitis in a tertiary care hospital - Subhradipta Bhattacharyya; Arup Ghosh (Asian Journal of Medical Sciences, 2023)
Background: Meningitis, inflammation of the meninges with systemic septicemia, from the bacterial, viral, or fungal origin, is a fatal disease in all age groups, particularly infants and children. The present study was done to evaluate the usage of antibiotics in pediatric patients with meningitis in a tertiary care hospital. Aims and Objectives: The study was conducted to evaluate the prescription pattern of antibiotics for pediatric patients suffering from meningitis. The efficacy of antibiotics, combination of antibiotics, and the resistance developed against them were reevaluated. Materials and Methods: An observational, noninterventional study with 34 pediatric patients (The mean age of the patients were 6.17 year. ±4.84 SD) admitted in Kalinga Institute of Medical Sciences (KIMS), Bhubaneswar from September 2012 to February 2014 were evaluated. Data were collected after the approval of the research protocol by the Institutional Ethics committee, KIMS from case sheets of patients from the ward as well as the Medical Record and Data section. Comparative statistical analysis was done by using student’s t-test in respect of data measured on a continuous scale. All differences with P<0.05 were labeled as statistically significant. Results: Ceftriaxone±ß lactamase inhibitor (βLI) (77.4%), and Cefoperazone±βLI (12.9%) were the most frequently used cephalosporin. In 55.8% of patients, three or more antibiotics in combination were given. Two drugs regimen like β lacatam+aminoglycoside in 23.5% of patients and β lactam+anti-Methicillin-resistant Staphylococcus aureus (MRSA) in 20.6% were given. Emerging resistance pattern against both Gram-positive cocci and Gram-negative bacilli to penicillins, cephalosporins, and aminoglycosides which are the primary first-line drugs has been observed. Conclusion: Very severe meningitis patients were treated with multiple antibiotics including anti-MRSA agents. High resistance (≥60%) was observed against β lactams.